Three case reports of infants with ankyloglossia affecting breastfeeding - Jamani, Nurjasmine Aida; Ardini, Yunita Dewi; Harun, Nor Asilah (Medical Journal of Malaysia, 2020)
Ankyloglossia is a congenital anomaly which may reduce or restrict the tongue tip mobility. The restricted mobility is caused by an unusual short, thick lingual frenum. This condition may cause various problems in infants including breastfeeding in the new-borns. This case report describes 3 cases of ankyloglossia affecting breastfeeding and highlights the experiences of the mothers and their difficulties in breastfeeding babies with it. Comprehensive feeding examination was accomplished, The primary cause of feeding issues was identified, and frenotomy intervention was provided. Post frenotomy, infants were able to breastfeed easily and this was beneficial in continuation of breastfeeding and pain reduction in mothers.